Thyroid Autoimmunity in the Context of Type 2 Diabetes Mellitus: Implications for Vitamin D - Konstantinos Toulis; Xanthippi Tsekmekidou; Evangelos Potolidis; Triantafyllos Didangelos; Anna Gotzamani-Psarrakou; Pantelis Zebekakis; Michael Daniilidis; John Yovos; Kalliopi Kotsa (International Journal of Endocrinology)
Vitamin D deficiency has been associated with both type 2 diabetes mellitus (T2DM) and autoimmune disorders. The association of vitamin D with T2DM and thyroid autoimmunity (TAI) has not been investigated. Thus, we aimed to explore the putative association between T2DM and thyroid autoimmunity (TAI) focusing on the role of 25-hydroxy-vitamin D (25(OH)D). Study population included 264 T2DM patients and 234 controls. To explore the potential association between 25(OH)D and thyroid autoimmunity while controlling for potential confounders—namely, age, gender, body mass index, and presence of T2DM—multivariate logistic regression analyses were undertaken. Patients with T2DM were younger (P<0.001) and had significantly lower 25(OH)D levels (P<0.001) and higher anti-TPO titers (P=0.005). Multivariable logistic regression analyses suggested that T2DM and 25(OH)D levels were significantly associated with the presence of thyroid autoimmunity. In an elderly population of diabetic patients and controls with a high prevalence of vitamin D deficiency/insufficiency, a patient with T2DM was found to be 2.5 times more likely to have thyroid autoimmunity compared to a nondiabetic individual and the higher the serum 25(OH)D levels were, the higher this chance was.